Sierra Leone : 2006 Article IV Consultation, First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Financing Assurances Review, and Request for Waiver of Nonobservance of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2007)
The 2006 Article IV Consultation, First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility of Sierra Leone reviews sustainability of higher economic growth and reduction of poverty. Sierra Leone has made progress in improving governance and transparency, but much remains to be done, particularly in the area of governance. Reforms guided by the recommendations of the recent Financial Sector Assessment Program should be given high priority. The authorities concurred that future borrowing should be limited to concessional terms to avoid another build-up of unsustainable debt.